A study of waste and delivery valve design modification to the pump performance - M. N., Harith; R. A., Bakar; D., Ramasamy; K., Kadirgama; Ma, Quanjin (IOP Publishing, 2018)
This paper objective is to share design revolution of waste and delivery valve that contribute to the overall pump performance. In this paper, 3 new designs of waste and delivery valve pump are presented with comprehensive internal flow analysis using computational fluid dynamics (CFD) simulation over 4 cases that have been deeply study for one of the design chosen. 4 cases involving opening and closing both valve or either one. 0.265m height size of customized waste valve with an opening limiter and spring was used to demonstrate cyclic closing and opening valve operation extended up to 0.164m gap. Based on result, this characteristics contribute to 10-20% waste water reduction and enhancement of flow rate height up to 80m. Apart from that this paper also share some of pressure (dynamic, total, static), velocity (x, y, z axis) simulation including the vector flow were under different flow cases.